Dynamics of morphobiological parameters of bream Abramis brama (Cyprinidae; Cypriniformes; Actinopterygii) in the Kapshagai reservoir (Balkhash basin) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The morphological and biological characteristics of fish are largely determined by environmental conditions. The study of the variability of fish makes it possible to assess their ecological plasticity and the state of the habitat. A comparative study of morphological variability in the temporal aspect of the bream Abramis brama (Linnaeus, 1758) from the Kapchagai reservoir was carried out. The state of biological indicators, plastic and counting characteristics of samples from 1974, 1992 and 2020 was studied. The method of principal components was used for statistical analysis. The 2020 sample is distinguished by better body condition, but smaller fish sizes. Over the past 28 years, there has been a significant change in the external morphology of bream. The hydrodynamic parameters and the shape of the head have changed. The noted changes may be the result of changes in the ecological niche. At present, the homeostasis of bream development is disturbed in the Kapchagai reservoir, however, high ecological plasticity allows this species to exist in changing environmental conditions